2023 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2023)
This article describes the public health impact of Alzheimer's disease, including prevalence and incidence, mortality and morbidity, use and costs of care, and the overall impact on family caregivers, the dementia workforce and society. The Special Report examines the patient journey from awareness of cognitive changes to potential treatment with drugs that change the underlying biology of Alzheimer's. An estimated 6.7 million Americans age 65 and older are living with Alzheimer's dementia today. This number could grow to 13.8 million by 2060 barring the development of medical breakthroughs to prevent, slow or cure AD. Official death certificates recorded 121,499 deaths from AD in 2019, and Alzheimer's disease was officially listed as the sixth‐leading cause of death in the United States. In 2020 and 2021, when COVID‐19 entered the ranks of the top ten causes of death, Alzheimer's was the seventh‐leading cause of death. Alzheimer's remains the fifth‐leading cause of death among Americans age 65 and older. Between 2000 and 2019, deaths from stroke, heart disease and HIV decreased, whereas reported deaths from AD increased more than 145%. This trajectory of deaths from AD was likely exacerbated by the COVID‐19 pandemic in 2020 and 2021. More than 11 million family members and other unpaid caregivers provided an estimated 18 billion hours of care to people with Alzheimer's or other dementias in 2022. These figures reflect a decline in the number of caregivers compared with a decade earlier, as well as an increase in the amount of care provided by each remaining caregiver. Unpaid dementia caregiving was valued at $339.5 billion in 2022. Its costs, however, extend to family caregivers’ increased risk for emotional distress and negative mental and physical health outcomes — costs that have been aggravated by COVID‐19. Members of the paid health care workforce are involved in diagnosing, treating and caring for people with dementia. In recent years, however, a shortage of such workers has developed in the United States. This shortage — brought about, in part, by COVID‐19 — has occurred at a time when more members of the dementia care workforce are needed. Therefore, programs will be needed to attract workers and better train health care teams. Average per‐person Medicare payments for services to beneficiaries age 65 and older with AD or other dementias are almost three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 22 times as great. Total payments in 2023 for health care, long‐term care and hospice services for people age 65 and older with dementia are estimated to be $345 billion. The Special Report examines whether there will be sufficient numbers of physician specialists to provide Alzheimer's care and treatment now that two drugs are available that change the underlying biology of Alzheimer's disease.